The Brazilian Deindustrialization in the Light of the Structuralist Tradition: A multisectoral analysis (2000-2018) - Marques Augusto Monteiro, João Guilherme; Zanchetta Borghi, Roberto Alexandre (Brazilian Keynesian Review, 2025)
This paper accomplishes an analysis of the Brazilian sectoral deindustrialization, based on the technological intensity differential, for the period 2000-2018. As theoretical framework the multisectoral studies are adopted, in the field of structuralist tradition, which evaluate the capacity of industrial sectors to promote economic growth in function of its level of technological intensity. By incorporating the contributions of multisectoral studies to the analysis of deindustrialization, this paper contributes to the debate, verifying the heterogeneity of this process between sectors and emphasizing the importance of evaluating the industrial composition. For the calculation of sectoral deindustrialization, input-output matrices are used as database. It is observed that deindustrialization is more accentuated in high-tech sectors, precisely those with greater capacity to promote and sustain economic growth. Moreover, it is concluded that the industrial productive structure is weakened in terms of the capacity to boost economic growth, because it is concentrated in sectors of medium-low technological intensity, while the sectors of medium-high and high technological intensity represent a reduced share of Brazilian industry. In this way, the severity of Brazilian deindustrialization and the importance of evaluating it in a disaggregated way are highlighted to comprehend its impacts over the economic growth of the country.